2012
DOI: 10.1063/1.4736582
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of temperature dependent domain wall dynamics in hard lead zirconate titanate piezoceramics

Abstract: Composition and orientation dependence of high electric-field-induced strain in Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 single crystals J. Appl. Phys. 112, 126102 (2012) Elastic, dielectric and piezoelectric characterization of single domain PIN-PMN-PT: Mn crystals J. Appl. Phys. 112, 124113 (2012) Scaling the dynamic response and energy harvesting potential of piezoelectric beams Appl. Phys. Lett. 101, 264104 (2012) High piezoelectric performance in a new Bi-based perovskite of (1−x)Bi(Ni1/2Hf1/2)O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…non-relaxor) systems show a frequency-dependent low temperature dielectric anomaly. For instance, the well-known -PbZr Ti O x x 1 3 (PZT) system shows a low temperature dielectric relaxation for different crystallographic structures (different x values) and dopants (donors and/or acceptors) [10][11][12][13]. A similar anomalous behavior has also been reported in NaNbO 3 [14], ( ) K, Na NbO 3 [15] [19], and other perovskite systems.…”
Section: Introductionsupporting
confidence: 58%
“…non-relaxor) systems show a frequency-dependent low temperature dielectric anomaly. For instance, the well-known -PbZr Ti O x x 1 3 (PZT) system shows a low temperature dielectric relaxation for different crystallographic structures (different x values) and dopants (donors and/or acceptors) [10][11][12][13]. A similar anomalous behavior has also been reported in NaNbO 3 [14], ( ) K, Na NbO 3 [15] [19], and other perovskite systems.…”
Section: Introductionsupporting
confidence: 58%
“…22 This observation proves that the nonlinear behavior is directly related to the extrinsic effect. 11 The nonlinear dielectric response is significant at temperatures at which the domain wall motion contribution becomes important, usually above 150 K. 23 Nonlinear dielectric response increases in the FO region as the temperature rises up to the PPB region, where the nonlinear response maximizes (this is particularly noticeable in ''), and then decreases again in the FT region.…”
Section: This Is the Post-print (Ie Final Draft Post-refereeing) Ofmentioning
confidence: 99%
“…43 However, it has been suggested that in hard PZTs that reversible domain wall movement is the dominant mechanism at room temperature as the material response does not adhere to Rayleigh law. 44 As the Rayleigh law is closely obeyed in the BF-KBT-PT system, it can be inferred that this system behaves more similarly to a soft PZT although driven at much higher excitation levels where lossy processes could become more prevalent, hence an increase in the contribution from reversible domain wall processes.…”
Section: Reconstructing the Temperature Dependence Of The Intrinsimentioning
confidence: 99%